2017
DOI: 10.1103/physreve.96.032218
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in magnitude series to assess nonlinearities: Application to multifractal models and heartbeat fluctuations

Abstract: The correlation properties of the magnitude of a time series are associated with nonlinear and multifractal properties and have been applied in a great variety of fields. Here we have obtained the analytical expression of the autocorrelation of the magnitude series (C_{|x|}) of a linear Gaussian noise as a function of its autocorrelation (C_{x}). For both, models and natural signals, the deviation of C_{|x|} from its expectation in linear Gaussian noises can be used as an index of nonlinearity that can be appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
4
28
0
1
Order By: Relevance
“…Finally, we introduce a parameter that can well measure the strength of nonlinear correlation, where the multifractal spectrum width ∆α q , that is a typical and widely used measure for such an analysis, is not able to discover such nonlinearities. Our results are in line with findings in recent studies [29,30].…”
Section: Introductionsupporting
confidence: 94%
See 3 more Smart Citations
“…Finally, we introduce a parameter that can well measure the strength of nonlinear correlation, where the multifractal spectrum width ∆α q , that is a typical and widely used measure for such an analysis, is not able to discover such nonlinearities. Our results are in line with findings in recent studies [29,30].…”
Section: Introductionsupporting
confidence: 94%
“…Recently, it has been shown that for a linearly correlated Gaussian series, such a symmetric relationship is also observed in the behavior of the second order correlation function of the magnitude C |x| (s) versus original series C(s) [29]. We argue that the method used in [29] is strongly dependent on the PDF of original series x, and thus before doing such an analysis one needs to replace rank-wisely the series values with a Gaussian ones, however in our approach no such a replacement is needed. Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Naturally, one may also study the auto-correlation of the fluctuations with DFA, by decomposing the time series into the sign series and the magnitude series [1,2,4,33]. Such an approach may provide further understanding associated with nonlinear and multi-fractal properties [34,35].…”
Section: Temporal Correlation Functions Of Stationary Statementioning
confidence: 99%